Apical Third Morphology and Intrusive Force Application: 3D Finite Element Analysis - A. Geramy (Tehran University of Medical Sciences, 2007)
Objective: Intrusion as a type of tooth movement is managed by different mechanotherapies during various treatment stages. The morphology of the apical third of the teeth to be intruded plays an important role in the risk of root resorption due to the raise of stresses. The main goal of this study was to compare various types of apical third of the teeth while loaded by an intrusive force. Materials and Methods: Four 3D Finite element models were designed with all supporting structures. Normal, needle form, short and sharp apices were considered. Intrusive forces of 0.5 N were applied and the VonMises stress along the mesial side of the root was assessed. Results: A tendency to show increased stresses at the cervical area of the teeth was noticed. The lowest stress was noticed in the blunt apex and the highest findings were shown to be in the needle form apex model. Conclusion: Normal variation in apical third of the teeth in intrusion can cause an increased stress level and also increased chance of root resorption which should be considered carefully in force applications.